The impact of a transversus abdominis plane block including clonidine vs. intrathecal morphine on nausea and vomiting after caesarean section: A randomised controlled trial. Issue 8 (August 2019) - Dereu, Domitille; Savoldelli, Georges L.; Mercier, Yannick; Combescure, Christophe; Mathivon, Stanislas; Rehberg, Benno
Abstract : BACKGROUND: Intrathecal morphine (ITM) is a widely used technique for postcaesarean section analgesia but entails a high risk of postoperative nausea and vomiting (PONV). The transversus abdominis plane (TAP) block is an alternative. OBJECTIVE: We tested the hypothesis that a TAP block including clonidine reduces the incidence of PONV after caesarean section when compared with ITM. DESIGN: A randomised, controlled, double-blinded study. SETTING: Geneva University Hospitals, Switzerland, from October 2013 to February 2017. PATIENTS: A total of 182 patients undergoing elective caesarean section were studied. Reasons for noninclusion were complicated pregnancy, contraindication to spinal anaesthesia or TAP block, extreme weight or height, allergy to any medication or previous median abdominal incision. INTERVENTIONS: Patients were allocated randomly to one of two groups (quadruple blinded): 100 μg of morphine added to the spinal local anaesthetic or a bilateral TAP block with 20 ml of ropivacaine 0.375% + 75 μg of clonidine on each side. MAIN OUTCOME MEASURES: The primary outcome measure was the total number of patients presenting with PONV at 24 h. Secondary aims were to compare other adverse effects (pruritus, respiratory depression, hypotension, bradycardia, sedation), analgesic efficacy and the quality of postoperative recovery. RESULTS: At 24 h, there was no significant difference between ITM and TAP groups in the total number of patients presenting with PONV: 17/92 patients (18.5%, 95% confidence interval 11.1 to 27.9) and 27/88 patients (30.7%, 95% confidence interval 21.3 to 41.4) in TAP and ITM groups, respectively ( P  = 0.065). Pain scores at 6 h and cumulative morphine consumption at 24 h were lower in the ITM group ( P  < 0.0001 for morphine consumption at 24 h). The incidence of hypotension was higher in the TAP group (54.3 vs. 29.2%, P  = 0.0006). Maternal satisfaction was high and not different between groups. CONCLUSION: A TAP block with clonidine and local anaesthetic does not reduce significantly the incidence of PONV compared with ITM. We confirm the superiority of ITM on acute postcaesarean section analgesia compared with a TAP block, even with clonidine as an adjunct. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT 01931215. Abstract : Supplemental Digital Content is available in the text